H.E. Bird : a chess biography with 1.198 games - Renette, Hans, 1977- (McFarland & Company, Inc., Publishers, 2016)
"This comprehensive first biography of Bird provides a detailed account of his personal life and a deeply researched coverage of his feats at the chess board. Almost 1,200 games are included, hundreds of them published here for the first time. Nearly 450 games--many of them thrilling all-out fights--are presented with a mix of contemporary and modern annotations"--